Type theory as a framework for modelling and programming - Ionescu, C; Jansson, P; Botta, N (Springer Nature, 2018)
In the context provided by the proceedings of the UVMP track of ISoLA 2016, we propose Type Theory as a suitable framework for both modelling and programming. We show that it fits most of the requirements put forward on such frameworks by Broy et al. and discuss some of the objections that can be raised against it.